Prospective Study of the Impact of Preoperative Nutrition on Postoperative Outcomes in Paediatric Surgery Using a Novel Two-axis Classification Scheme - Chacko, Benjamin; Zameer, M. M.; Vinay; D'cruz, Ashley L. J.; Rao, Sanjay (Journal of Indian Association of Pediatric Surgeons, 2025)
ABSTRACT Background: Malnutrition is a significant concern in the hospitalized surgical cohort. Despite this there is no standardized scheme tailored for the pediatric surgical cohort. This study evaluated the feasibility to of the novel two-axis scheme to fill the lacunae in pediatric nutritional assessment. Aims: The aim of this study is to study the effect of the preoperative nutritional status on the clinical outcomes. Materials and Methods: This is a prospective, observational, and cohort study of all pediatric patients undergoing surgery at our center from January 2021 to September 2022. Preoperative anthropometry was measured and all subjects were classified using the two-axis scheme incorporating body mass index and height z-scores into nonoutliers or one of the four outlier groups: underweight short, underweight tall, overweight short, and overweight tall. All complications within 30 days postsurgery were recorded and graded by the Clavien-Dindo classification. Results: The study included a total of 827 patients who underwent 1022 surgeries, 70.5% being males. About 33% of the cohort was under 5 years of age. Overall incidence of complications was 10.1% with underweight short group having the highest (19.7%). Underweight short group had higher incidence of composite and healthcare-associated infections (P < 0.05) and higher odds of all types of complication in comparison to the nonoutliers. No significant relation was noted between the nutritional groups and the severity of the complication. Conclusions: This study supported the predictive value and feasibility of this novel two-axis nutritional classification scheme in the pediatric surgical outcomes. The underweight short subjects are at higher risk of developing postoperative complications.